Detection of alcohol content in saliva via chemical and enzymatic methods - Teo, Hwang Bin. (2011)
Due to the close correlation between the ethanol concentration in blood and that in saliva, testing saliva samples becomes a good approximation of measuring the test subject’s blood alcohol content. Two combinations of colorimetric reagents were selected to be tested with regards to their detection and ability to show pronounced colour changes as results: potassium dichromate with sulphuric acid; and alcohol oxidase with horseradish peroxidase and 3, 3’, 5, 5’ tetramethylbenzidine. Acidified potassium dichromate was found to have incomplete colorimetric reactions in the liquid phase due to slow reaction rates at low chemical concentrations of ethanol and hence was deemed unsuitable for application in membrane strips even when the concentrations of the reagents have been changed. The enzymatic reaction was able to produce strong colorimetric changes within ten minutes even with low ethanol concentrations of normally found in saliva and various differing amounts of the reagent components were tested to find the best combination which gave the most recognisable colorimetric change. It was found that halving the amount of horseradish peroxidase gave the best distinction as compared to manipulating other reagent amounts. Finally, a limited implantation of the reagent enzymes on cellulose membrane strips was carried out with a focus on investigating the shelf life of the dried enzymes by dissolving them in potassium buffer solutions with 30% sucrose by weight, which produced enzyme-embedded test strips effective for up to one week.